Pemanfaatan Media Pembelajaran Cisco IT Essential Virtual Desktop untuk Meningkatkan Hasil Belajar - Rizqiawan, Dwi Wisuda; Saepuloh, Luthpi; Wulandari, Heni (utile: Jurnal Kependidikan, 2018)
The background of this research are (1) Learners do not understand computerassembly material, (2) Insufficient facilities and infrastructure, (3) Teaching time istrimmed due to curriculum change. The purpose of the research is to know the effect ofCisco IT Essential Virtual Desktop learning media to the learning result of class X TKJ Bstudents in Computer and Basic Network subject especially in computer assemblingmaterial. The research method used is Quantitative approach using Pretest-Posttest One-Group design. The population in this study amounted to 67 students (all classes X TKJ)and the sample was 31 students (class X TKJ B). Data analysis using simple linearregression. The results of this study are: an increase in learning outcomes of learners usinglearning media Cisco IT Essential Virtual Desktop. Seen from the average value beforetreatment was 38.70 and after treatment experienced a drastic increase of 72.58. And theincrease of 33.87.